Val d’Hérens (Switzerland): A history of Missed (tourist) Transitions - Marjolaine Gros-Balthazard; Caterina Franco; Anouk Bonnemains (Revue de Géographie Alpine)
Since the early 20th century, various transformations (economic, social, environmental, climatic etc.) have changed the way people live in the Alpine regions. While tourism, as a development model, has been one of the vectors of these transformations, it is now adapting to address socio-environmental and climate issues. Based on a case study of the Val d’Hérens in the Swiss Valais and adopting a diachronic perspective, this article examines the factors behind three phases of past tourism transformations, which we propose to view as territorial transitions. The originality of this work lies in its focus on a range of unfulfilled tourism development projects in a mountain valley drawn up between 1900 and 2020. The study of the relationships between the (material, ideal and institutional) dimensions within the concept of territory and constitutive of the projectual processes makes it possible to reveal the explanatory factors of the tourist transitions, which did not happen but were “missed“. It allows us to emphasise the value of diachronic analysis and the need to recognise the multi-scalar nature of transitions. In addition, it presents opportunities for reflection on the lessons learned from what we might consider to be failures and their influence on territorial dynamics.